Implications of the Application of the Ummi Method in Learning Tahfidz Qur'an at Muhammadiyah Elementary School Kalikajar Wonosobo - Wulandari Antonia, Evy; Suyud El Syam, Robingun; Kholil, Asyhar (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
Many methods have been created to facilitate learning to read and memorize the Qur'an, one of which is the Ummi method. It is interesting to study the implications of this method for memorizers of the Qur'an. This article uses a qualitative descriptive research type with data sources from interviews, observations and documentation, then analyzed qualitatively with data reduction, presentation and validation steps. The research results show that the implications of the Ummi method in learning the Tahfidz Qur'an, which show positive results, with 19 students completing Juz 29 and 30, are evidence that this method is effective in improving the ability to memorize and understand the Qur'an. These findings confirm that this method has the potential to be an effective and reliable Tahfidz learning method. Recommendations for the development of this method for the future are suggested based on the findings of existing analysis data such as strengthening the duration of practice, variations in methods, or increasing individual guidance for students who have difficulty.